THE SUBTITLING STRATEGIES USED IN INDONESIAN FILM - Noni Agustina; Joni Joni (STKIP Siliwangi, 2019)
The social phenomena can be represented through film providing images, soundtrack, voice- over, dance, and some art such as theatrical dan fine art. The Indonesian film played in XXI since 2017 must have English subtitling because the viewers nowadays are not only Indonesian people but also foreigner. The film subtitling is challenging because it is different from the other translation medium. A subtitler requires an appropriate translation strategy. Thus, this study aims to explore the subtitling strategies used in Indonesian film. The approach employed was qualitative with content analysis as a research design. The data used was English subtitling of ‘A Man Called Ahok’ film. The result showed that the dominant substitiling strategies used were repetition indicating the literal translation and addition strategy showing more information given. Respectively, transmutation and detraction strategies are also employed. Former indicated some changes in internal order such as lexical change, passive to active, etc. The latter showed deletion or condension unnecessary or inrelevant information. Substitution strategy is the least used in subtitling which it indicates lack of pharaprasing. This study offers the theoretical and practical contribution on subtitiling strategies especially from Bahasa Indonesia to English. Keywords: Film, audiovisual translation, subtitling, translation strategies.